Perinatal Illicit Drug and Marijuana Use: An Observational Study Examining Prevalence, Screening, and Disclosure. Issue 1 (January 2017) - Chang, Judy C.; Holland, Cynthia L.; Tarr, Jill A.; Rubio, Doris; Rodriguez, Keri L.; Kraemer, Kevin L.; Day, Nancy; Arnold, Robert M.
Purpose: To assess use, screening, and disclosure of perinatal marijuana and other illicit drugs during first obstetric visits. Design: Observational study that qualitatively assesses provider screening and patient disclosure of substance use. Setting: Study sites were five urban outpatient prenatal clinics and practices located in Pittsburgh, Pennsylvania. Participants: Pregnant patients and obstetric providers were recruited as participants. Methods: We audio recorded patient-provider conversations during first obstetric visits and obtained patient urine samples for drug analyses. Audio recordings were reviewed for provider screening and patient disclosure of illicit drug use. Urine analyses were compared with audio recordings to determine disclosure. Results: Four hundred and twenty-two pregnant patients provided complete audio recordings and urine samples for analyses. Providers asked about illicit drug use in 81% of the visits. One hundred twenty-three patients (29%) disclosed any current or past illicit drug use; 48 patients (11%) disclosed current use of marijuana while pregnant. One hundred and forty-five samples (34%) tested positive for one or more substances; marijuana was most commonly detected (N = 114, 27%). Of patients who tested positive for any substance, 66 (46%) did not disclose any use; only 36% of patients who tested positive for marijuana disclosed current use. Conclusion: Although marijuana is illegal in Pennsylvania, a high proportion of pregnant patients used marijuana, with many not disclosing use to their obstetric care providers.